Aplikasi Gofutsal Untuk Pemesanan Lapangan Futsal Berbasis Android - Bagus Kristomoyo Kristanto; Erikson Paulus Yosep; Daniel Rudiaman Sijabat (J-INTECH ( Journal of Information and Technology), 2021)
Futsal is currently a sport that is in great demand by various ages in Indonesia, including in Malang. With the development of the sport of futsal, it has also had a positive impact on business people, many of whom take advantage of this condition to open business land, one of which is making futsal fields for rent. Futsal field rental service providers are competing to attract enthusiasts with the various facilities offered. However, all of these are not supported by good means of conveying information. The rental process is also quite troublesome for the community due to the obstacles that are often encountered. Bookers have to come in person to see the schedule availability, this can take a while. In this research, an Android-based GoFutsal application will be designed. Making the GoFutsal application uses data collection, problem analysis and software design along with testing the software. The results of this study are in the form of a futsal field reservation application that can be accessed via the Android platform. The results of the Black Box trial conducted on the features of the Gofutsal application went well and in accordance with its function. With the GoFutsal application, it is hoped that it can help the public in getting information and can simplify the process of ordering futsal fields. Keywords : Futsal, Futsal Court, Android Application, Black Box